Effect of diethylaminoethyl-dextran coated liposomes on the rheological properties of carbopol gel - Menon, Premanarayani; Teo, Yin Yin; Misran, Misni (Kerschensteiner Verlag, 2018)
Liposomal gel has played an important role in administration of drugs via topical and transdermal routes. Incorporation of liposome into gel not only has overcome the liquid nature of liposomal dispersion but also helped to preserve the original structure of liposome. In this study, we formulated a liposomal gel consisting of Carbopol gel and a diethylaminoethyl dextran (DEAE-DX) coated liposome. The effect of coated and non-coated liposomes on the rheological properties of Carbopol gel was investigated. The rheological results indicated that incorporation of liposomes into Carbopol gel modified the viscoelastic and flow behaviour of the gel significantly. Apart from that, liposomal gel consisting of DEAE-DX coated liposomes exhibited more solid-like behavior compared to the non-coated liposomal gel. Incorporation of DEAE-DX coated liposomes increased the yield stress of liposomal gel compared to non-coated liposomes. This supports the findings obtained from the amplitude and frequency tests whereby addition of DEAE-DX enhanced the rigidity of the gel so that the resultant gel was more resistant to flow.